Analysis of the Effects of Hydrocarbon Chain on Foam Properties of Alkyl Polyglycosides. Issue 3 (25th March 2017) - Zhou, Yawen; Wang, Shan; Lv, Mengdie; Niu, Jinping; Xu, Baocai
Abstract: The influence of surfactant structure on foam properties of different alkyl polyglycosides (APGs) in aqueous solutions was studied. Foamability, foam stability, and foam morphology were analyzed using the FoamScan method. Results showed that the foamability, foam stability, and the liquid carrying ability of long‐chain APGs are higher than those of short‐chain APGs. Foam morphology analysis showed that the foam produced by short‐chain APGs is more unstable than the foam generated by long‐chain APGs. Long‐chain APGs have stronger intermolecular cohesion force, stringency, and ductility than short‐chain APGs.